Elasticity and Causality Among Electricity Generation from Renewable Energy and Its Determinants in Malaysia - Bekhet, Hussain Ali; Harun, Nor Hamisham (International Journal of Energy Economics and Policy, 2017)
Renewable energy is a significant issue in attaining low-carbon emissions for Malaysia's economic development path. Therefore, this study investigates the determinants (capital, labour, economic growth, and financial development), which has an influence on renewable energy generation, using time-series data from 1982 to 2015 period. The augmented Cobb–Douglas production function, F-bound test, and vector error correction model are employed to achieve the objectives of the study. The result of the analysis indicates a dynamic relationship among these variables. The long-run elasticity of capital and labour promotes renewable energy generation, while the responsiveness of economic growth and financial development undermine electricity generation from renewable energy. Furthermore, there is long-run bidirectional causal relationship between capital and renewable energy generation. Similarly, the feedback effect is found between labour and electricity generation from renewable energy. Economic growth and financial development are found to influence renewable energy generation. Accordingly, the Malaysian government should pursue policies to enhance the utilization of renewable energy sources toward national electricity supply security and sustainable socio-economic development. Keywords: Malaysia, renewable energy, financial development, sustainable energy, elasticity, causality JEL Classifications: E44, Q4, Q43